2010 Proceedings IEEE INFOCOM 2010
DOI: 10.1109/infcom.2010.5462165
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Waveband Switching in Optical Ring Networks

Abstract: Waveband switching saves port costs in optical crossconnects by grouping together a set of consecutive wavelengths and switching them as a single waveband. Previous work has focused on either uniform band sizes or non-uniform band sizes considering a single node. In this paper, we show that such solutions are inadequate when considering the entire network, and present a novel framework for optimizing the number of wavebands in a ring network for deterministic traffic. We then consider a specific type of traffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Specifically, in [13], solutions for both uniform and non-uniform waveband switching are presented whereas [11] only considers non-uniform wavebands. In [12], the waveband design problem is considered in the context of optical ring networks for non-uniform wavebands. To the best of our knowledge, this is the first work on waveband design for optical mesh networks.…”
Section: Motivation and Contributionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, in [13], solutions for both uniform and non-uniform waveband switching are presented whereas [11] only considers non-uniform wavebands. In [12], the waveband design problem is considered in the context of optical ring networks for non-uniform wavebands. To the best of our knowledge, this is the first work on waveband design for optical mesh networks.…”
Section: Motivation and Contributionmentioning
confidence: 99%
“…In [11][12][13], the authors showed the benefits of using non-uniform wavebands. Izmailov et al [11] investigated the case of nonuniform wavebands at a single node, which is the source of lightpaths to multiple destinations, and also discussed non-uniform wavebands in terms of waveband utilization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the worldwide fiber deployment and advancing dense WDM technologies, one of the major challenges faced by T-OXCs is the dramatic increase of the node size, cost and control complexity. To address such issues, waveband switching (WBS) in conjunction with multi-granular optical cross-connects (MG-OXCs) is introduced [2]- [12]. One fundamental problem in WBS networks is the routing and wavelength/waveband assignment (RWA), which refers to the process of assigning wavelengths and routing wavelengths through intermediate nodes to satisfy the traffic demands.…”
Section: Introductionmentioning
confidence: 99%